Nickel and ocean warming affect scleractinian coral growth. Issue 1 (15th July 2017) - Biscéré, T.; Lorrain, A.; Rodolfo-Metalpa, R.; Gilbert, A.; Wright, A.; Devissi, C.; Peignon, C.; Farman, R.; Duvieilbourg, E.; Payri, C.; Houlbrèque, F.
Abstract: The sensitivity of corals and their Symbiodinium to warming has been extensively documented; however very few studies considered that anthropogenic inputs such as metal pollution have already an impact on many fringing reefs. Thus, today, nickel releases are common in coastal ecosystems. In this study, two major reef-building species Acropora muricata and Pocillopora damicornis were exposed in situ to ambient and moderate nickel concentrations on a short-term period (1 h) using benthic chamber experiments. Simultaneously, we tested in laboratory conditions the combined effects of a chronic exposure (8 weeks) to moderate nickel concentrations and ocean warming on A. muricata . The in situ experiment highlighted that nickel enrichment, at ambient temperature, stimulated by 27 to 47% the calcification rates of both species but not their photosynthetic performances. In contrast, an exposure to higher nickel concentration, in combination with elevated temperature simulated in aquaria, severely depressed by 30% the growth of A. muricata . Highlights: Nickel played a dual role on coral physiology according to the surrounding water temperature. At ambient temperature nickel enrichment increased the calcification rates of both tested species. The combination of warming and nickel reduced by 30% the growth rates of A. muricata.